Evidence-based design of a mobile emergency operating room: The Surgery on Wheels concept for disaster response - Nur Ikhsani Rahmatika; Riski Arifin; Meilya SIlvalila; Rifa Nazamudin; Alya Samsurizal (TDMRC, Universitas Syiah Kuala, 2025)
Indonesia is one of the countries most vulnerable to disasters, where the destruction of health infrastructureparticularly surgical facilitiesoften hampers emergency medical response. During disasters, the sharp increase in patients contrasts with the limited availability of sterile and functional operating rooms. This study focuses on Aceh as a case study due to its high disaster exposure and logistical challenges, while proposing a design model adaptable to other hazard-prone regions. The research adopts a qualitative, evidence-based design (EBD) approach to develop a mobile emergency operating room (MEOR) that integrates functionality, mobility, and sustainability. The proposed design utilizes a modified 20-foot shipping container equipped with a hydraulic expansion system and an inflatable tent module to enhance operational flexibility. Supported by interdisciplinary collaboration among architects, engineers, medical professionals, and disaster specialists, the design emphasizes five key parameters: mobility, modularity, portability, safety, and comfort. Findings demonstrate that the Surgery on Wheels concept provides a viable and deployable solution for emergency surgical services in disaster-stricken and remote areas. It offers an environmentally conscious model that supports both disaster response and public health emergencies such as pandemics, advancing the discourse on resilient and sustainable healthcare infrastructure in developing regions.